2020
DOI: 10.1002/jgc4.1317
|View full text |Cite
|
Sign up to set email alerts
|

Informing models of cancer genetics care in the era of multigene panel testing with patient‐led recommendations

Abstract: The study describes patient‐reported experiences and recommendations to improve the genetic counseling and multigene panel testing (MGPT) process. A descriptive mixed‐method study with concurrently collected and integrated qualitative and quantitative data was conducted. Eligible participants were English‐speaking adults with a breast or gynecologic cancer diagnosis who had received genetic counseling and testing with a MGPT from one Comprehensive Cancer Center. Satisfaction with the genetic counseling, geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The positive experience subscale is reverse scored so that a higher score indicates a less positive experience. In the parent study, the MICRA was found to be reliable with a Cronbach alpha of 0.83 for the total scale, 0.88 for the distress subscale, 0.78 for the uncertainty subscale, and 0.77 for the positive experience subscale [21].…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…The positive experience subscale is reverse scored so that a higher score indicates a less positive experience. In the parent study, the MICRA was found to be reliable with a Cronbach alpha of 0.83 for the total scale, 0.88 for the distress subscale, 0.78 for the uncertainty subscale, and 0.77 for the positive experience subscale [21].…”
Section: Methodsmentioning
confidence: 94%
“…Specific cancer genetics knowledge needs were identified by calculating the proportion of participants who selected the correct response for each item on the KnowGene scale. Based on findings in the parent study, the following factors were assessed for potential associations with MICRA and KnowGene scores: marital status (married/partnered vs. not), educational attainment (college graduate vs. not), annual household income (less than $50,000 vs. $50,000 or more), race/ethnicity (white, non-Hispanic vs. not), pathogenic gene variant (BRCA vs. not), and genetic test result (positive vs. not, negative vs. not, and VUS vs. not) [21]. Consistent with the parent study, a square root transformation was applied to MICRA total and subscale scores to account for positively skewed distributions of these scores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations